PENERAPAN APLIKASI “ VIRTUAL TRADING ” STOCKBIT PADA MATA KULIAH PRAKTIKUM PASAR MODAL - Agus Baskara; Purba Andy Wijaya (UIR PRESS, 2022)
This research examined the use of the Stockbit virtual trading application as a teaching tool in a practical capital market course for Accounting Education students of Universtas Islam Riau. The purpose of this research is to find out and analyze the ease of investing in stocks on the capital market through the implementation of a virtual trading application (simulation) for students as novice investors. The study used a descriptive qualitative analysis method. The research creates a stock investment model using virtual trading (simulation) through the stockbit application so that students can learn about the application model in increasing their investment interest as a novice investor. The results found that the virtual trading application was a convenient and zero-risk way for students to learn about investing and stock trading as novice investors, also indicated that the application could increase students' interest in investment and provide a better understanding of the investment process. Future research could expand the scope of the study to include a real capital market investment analysis method and investigate how students can maximize profits and minimize risks when investing